Rare and life-threatening iliac vein stent infection following radiotherapy: a case report emphasizing clinical urgency and preoperative stent evaluation - Liao, Jianyu; Ma, YuKui; Wu, Zhoupeng; Wang, Xinyan; Zhao, Jichun (Frontiers in Cardiovascular Medicine, 2025)
This case report discussed a 43-year-old female who underwent multiple radiotherapy sessions after cervical cancer surgery and experienced serious complications due to simultaneous iliac vein stent placement immediately after thrombus aspiration without adequate evaluation of the indication for stent placement. Two months after radiotherapy, the patient developed right lower limb edema and pain, which led to the discovery of an iliac vein thrombosis. Subsequent stent placement without thorough evaluation resulted in severe complications, including infection and sepsis. Despite initial symptom relief, the patient was readmitted with high fever and severe pain, and imaging revealed gas around the stent, indicating infection. An exploratory laparotomy uncovered a large abscess and a colonic fistula. The stents were removed, and the patient underwent aggressive anti-infection treatment involving meropenem and vancomycin, along with surgical repair of the fistula. This case highlights the importance of accurate diagnosis and careful consideration of stent placement in preventing severe outcomes, including the rare but serious risk of venous stent infections requiring surgical intervention.